Model Teams Games Tournament (TGT) Aided by Audio Visual Media on Learning Activeness of Elementary School Students: Model Teams Games Tournament (TGT) Berbantuan Media Audio Visual Terhadap Keaktifan Belajar Siswa Sekolah Dasar - Lestari, Dewi Ayu; Setiyawati, Enik (Indonesian Journal of Education Methods Development, 2023)
This research is motivated by a conventional science learning model that is teacher-centered, so that the level of student learning activity is still low, learning activity is influenced by teachers who can stimulate students to be more active in learning, discussing, expressing opinions, curiosity, seeking information. new (Zaeni 2017, Hidayah 2017). This study aims to determine the effect and how much influence the TGT learning model assisted by audio-visual media has on science learning activities at SDN Kepunten Tulangan for the 2021/2022 academic year. This study uses a quantitative research method of pre-experimental design, one-shot case study which is given posttest treatment, to determine the effect and magnitude of the influence the researcher uses the t-test one sample t- test to determine the effect of the TGT learning model assisted by audio-visual media on student learning activities. which obtained a significant value (2 – tailed) of 0.023 <0.05, and a tcount of 4.333 > ttable 2.04523, so it can be concluded that there is a positive and significant effect of the TGT learning model assisted by audio-visual media on student learning activities at SDN Kepunten Tulangan. In the F and R square tests to find out how much influence the TGT learning model has, the significant value is 0.00 < 0.05 and the R Square value is 0.929 or equal to 92%, which means that the TGT learning model assisted by audio-visual media has a major influence, namely 92% on student learning activity. So in conclusion, the TGT learning model assisted by audio-visual media on science learning activities for class V at SDN Kepunte has an effect of 92%.